Edukasi Bahaya Hepatitis Akut Di Unit Pelaksana Teknis Daerah Puskesmas Panarung Kota Palangka Raya - Turnip, Oktaviani Naulita; Nawan; Hanasia; Praja, Rian Ka; Martani, Natalia Sri; Furtuna, Dewi Klarita (Jurnal Pengabdian Kampus, 2023)
Hepatitis is a type of acute disease caused by a virus. Hepatitis virus itself is divided into several types, namely Hepatitis A, B, C, D, and E. The global prevalence of hepatitis is reported to be 2 billion patients in the world, 240 million people with chronic hepatitis B, followed by hepatitis C with 170 million patients. Every year, 1.5 million people die from hepatitis. Indonesia has the highest hepatitis B endemicity, making WHO set a global level evaluation of hepatitis control every two years. In early 2022, a case of hepatitis was found that was claimed to be acute hepatitis. The first case of acute hepatitis was reported in the United Kingdom and was designated as an Extraordinary Event in 2022. Cases of acute hepatitis spread to various countries in the world, including Indonesia. A total of 18 suspected cases of hepatitis were reported in North Sumatra, West Sumatra, Bangka Belitung Islands, DKI Jakarta, West Java, East Java, East Kalimantan, and DKI Jakarta. The main transmission of acute hepatitis is thought to be through body fluids, so the Ministry of Health has initiated procedures to prevent the transmission of acute hepatitis among the community, especially children. The low public understanding of the dangers of acute hepatitis makes us the UPR FK Microbiology team to provide understanding and education to the public regarding the dangers of hepatitis, handling, prevention and management of acute hepatitis if it occurs in the community.